Dataset of concerns for privacy information practices and consumer behavior in online market: A survey in Vietnam - Bui Thanh Khoa; Tran Viet Anh; Tran Trong Huynh (Data in Brief, 2024)
This dataset presents survey results on concerns for consumer privacy information practises in business, online trust; and purchase intention in the online marketplace in Vietnam. The raw data was collected via an online questionnaire of 467 respondents aged 18 and over recruited randomly. The survey included questions on demographic attributes as well as ratings and rankings for various statements related to privacy information concerns, such as Collection, Unauthorized secondary use (internal), Improper Access, Error; consumer online trust; and purchase intention when shopping online. The de-identified dataset is available in CSV format, including the question/statement text, collection method details, and coded response values. This novel dataset further investigates the impact of privacy information concerns on consumer behaviors in an emergent Southeast Asian e-commerce market. As one of the first collections of empirical data focused distinctly on perspectives within Vietnam, this dataset has high reuse potential for research on information privacy attitudes, responses, and needs within the country and in comparison to regional/global trends.